Online Teaching during Covid-19: An Analysis of Teachers’ Strategies In Teaching English for Students of English Business Class - Sri Mulyati (Universitas Batanghari Jambi, 2021)
The purpose of this current study was to to Analysis and to know the teacher's strategy in online learning english during the Covid 19 pandemic. This study’s approach was descriptive qualitative on survey research to thirty students of english business class. Teacher’s strategies in online teaching can be seen from a variety of strategies used for example: 1) teacher strategies in explaining lessons. 2) the teacher's strategies of giving assignments. 3) teacher’s strategies in providing grades.Then when explaining the discussion online so that it can be understood, and the obstacles experienced by the teacher when carrying out online learning teaching and learning activities during the Covid 19 pandemic. The participants are the students of english business class Lesson.